A semiotic reading of the multitude - da Silva, Alexandre Rocha (2016)
A semiotic reading of the multitude aims to problematize the functions of the incommensurable in semiosis. This involves questioning the problems of immanence, the rule of mediation that characterizes the contemporary semiotic thought and deconstruction of identities operated by queer theories. Therefore, methodologically, (1) we present the concepts of multitude developed by Charles Sanders Peirce, Antonio Negri and Michael Hardt; (2) we discuss the descriptive character of Peirce’s phaneroscopic categories to propose the Zeroness as the condition and immanence of all semiosis; (3) we identify the double side – virtual and mediated – of the singularity and (4) we show how the singularity, which is a potentiality, gives rise to identities in semiosis. It is the inseparable feature of singularity, identity and beliefs/habits that allows this article to report false dichotomies and affirm perspectivism as a fundamental horizon for semiotic studies of the multitude.